Gamification Design with a Domain-Driven Engineering Approach - Aguiar, Pedro Guilherme Pinto Ferraz de (2019)
Companies use a variety of methods and processes to improve the quality of their services, which, in turn, would increase the satisfaction of their users and hence their popularity. One of the enhancements that have been used in recent years is known as gamification. With the benefit of being virtually independent of business types, one of the goals of gamification is to solve user engagement issues. Even so, companies fail to achieve their goals after instantiating gamification into their services, and one cause is related to poor gamification design. The main objective of the developed project was to acquire and develop a possible solution to this problem through the use of a specific set of methods, technologies and the Model-Driven Engineering (MDE) approach. In this sense, in-depth research was done into previous gamification applications and other previous attempts to solve the problem at hand. Several gamification concepts were analyzed, gathering as much data as possible about the subject before the conceptualization of the solution’s domain through an MDE approach.